Big Five Personality Predictors of Career Readiness Among Agricultural Graduate Students - Muhammed Amina; Safna Vatakke Kandy Meethal; P K Smija; Manju Mary Paul; Allan Thomas (Indian Journal of Extension Education, 2025)
Personality traits greatly influence how a graduate selects, adapts, grows and flourishes in their professional career path. The study conducted in 2025 examined the relationship between personality traits and career readiness among 120 final year agricultural graduates of Kerala Agricultural University, corresponding to a ±8% margin of error at a 95% confidence level, using the Big Five Personality framework. Results showed higher mean scores in agreeableness (3.68) and openness (3.40), with no significant gender differences (p > 0.05). Analysis identified agreeableness (β = 0.354, p = 0.001), openness (β = 0.390, p = 0.004), and conscientiousness (β = 0.300, p = 0.021) as significant predictors of career readiness. Correlational analysis showed positive associations between agreeableness (r = 0.728, p < 0.01), openness (r = 0.665, p < 0.01), and conscientiousness (r = 0.413, p < 0.05) and career readiness. Independent-samples t-tests showed no significant gender differences across the Big Five traits at the 5% level. However, conscientiousness (d = 0.45) and neuroticism (d = –0.54) showed moderate effect sizes, indicating practical gender-based differences. The study highlights the value of soft skills, industry exposure, and personal and career development programmes in enhancing agricultural graduates’ career readiness and competence.